2008
DOI: 10.1111/j.1462-2920.2008.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of a new bacterial candidate division by an anaerobic sludge digester metagenomic approach

Abstract: We have constructed a large fosmid library from a mesophilic anaerobic digester and explored its 16S rDNA diversity using a high-density filter DNA–DNA hybridization procedure. We identified a group of 16S rDNA sequences forming a new bacterial lineage named WWE3 (Waste Water of Evry 3). Only one sequence from the public databases shares a sequence identity above 80% with the WWE3 group which hence cannot be affiliated to any known or candidate prokaryotic division. Despite representing a non-negligible fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
(59 reference statements)
0
18
0
2
Order By: Relevance
“…Sundberg et al (2013) found that bacterial OTUs (3% dissimilarity) clustered from the unclassified Bacteria sequences from different digesters were not closely related, accounting for an average of 33% (12-48%) and 10% (2-41%) of the bacterial sequences in full-scale anaerobic digesters fed with sewage sludge (n=7) and various organic wastes (n=14), respectively. Guermazi et al (2008) used a metagenomic approach to discover and characterize a new bacterial candidate division WWE3, which could not have been detected using traditional 16S rDNA PCR primers or FISH probes because of their unusual 16S rRNA gene. Based on the HTS data, new PCR primers and FISH probes were designed for the quantification and visualization of these novel bacteria in various environments.…”
Section: Novel Microorganismsmentioning
confidence: 99%
“…Sundberg et al (2013) found that bacterial OTUs (3% dissimilarity) clustered from the unclassified Bacteria sequences from different digesters were not closely related, accounting for an average of 33% (12-48%) and 10% (2-41%) of the bacterial sequences in full-scale anaerobic digesters fed with sewage sludge (n=7) and various organic wastes (n=14), respectively. Guermazi et al (2008) used a metagenomic approach to discover and characterize a new bacterial candidate division WWE3, which could not have been detected using traditional 16S rDNA PCR primers or FISH probes because of their unusual 16S rRNA gene. Based on the HTS data, new PCR primers and FISH probes were designed for the quantification and visualization of these novel bacteria in various environments.…”
Section: Novel Microorganismsmentioning
confidence: 99%
“…The increase in the number of CP over the last 10 years can be attributed in part to the subdivision of one major clade, initially referred to as OP11 (5), that is now recognized to comprise several phyla, including OP11, OD1, and SR1 (6). Some CP, such as TM7, are relatively well defined (5), while others, including WWE3 (7), and PER (8), have only recently been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…CP organisms have been detected by 16S rRNA gene sequencing surveys spanning a wide array of environment types, including the human oral microbiome (9, 10), the mammalian gut (11), bioreactors (7, 12, 13), freshwater lakes (14, 15), hypersaline microbial mats (1), and deep-sea vents (16). Targeted 16S rRNA gene primer assays have documented diversity within the CP and assessed the abundance of these organisms in certain environments, especially under anoxic and sulfidic conditions (6, 7, 1315, 17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…(Maidak et al, 1994); an 'in-house' database with sequences obtained from anaerobic digesters (Chouari et al, 2003(Chouari et al, , 2005aGuermazi et al, 2008).…”
Section: Sequence Analysismentioning
confidence: 99%